Answer:
x-y=4
and
x+y=32 is <u>your</u><u> </u><u>equation</u>
<u>d</u><u>i</u><u>f</u><u>f</u><u>e</u><u>r</u><u>e</u><u>n</u><u>c</u><u>e</u><u> </u><u>o</u><u>f</u><u> </u><u>t</u><u>w</u><u>o</u><u> </u><u>n</u><u>u</u><u>m</u><u>b</u><u>e</u><u>r</u><u> </u><u>=</u><u>x-y</u><u> </u><u>is</u><u> </u><u>equal</u><u> </u><u>to</u><u> </u><u>4</u>
<u>s</u><u>u</u><u>m</u><u> </u><u>o</u><u>f</u><u> </u><u>t</u><u>w</u><u>o</u><u> </u><u>n</u><u>u</u><u>m</u><u>b</u><u>e</u><u>r</u><u>=</u><u>x</u><u>+</u><u>y</u><u> </u><u>i</u><u>s</u><u> </u><u>e</u><u>q</u><u>u</u><u>a</u><u>l</u><u> </u><u>t</u><u>o</u><u> </u><u>3</u><u>2</u>
<u>x</u><u>-</u><u>y</u><u>=</u><u>4</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>(</u><u>1</u><u>)</u>
<u>x</u><u>+</u><u>y</u><u>=</u><u>3</u><u>2</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>(</u><u>2</u><u>)</u>
<u>a</u><u>d</u><u>d</u><u>i</u><u>n</u><u>g</u><u> </u><u>equation</u><u> </u><u>1</u><u> </u><u>a</u><u>n</u><u>d</u><u> </u><u>2</u>
<u>x</u><u>-</u><u>y</u><u> </u><u>+</u><u>x</u><u>+</u><u>y</u><u>=</u><u>4</u><u>+</u><u>3</u><u>2</u>
<u>2</u><u>x</u><u>=</u><u>3</u><u>6</u>
<u>x</u><u>=</u><u>3</u><u>6</u><u>/</u><u>2</u><u>=</u><u>1</u><u>6</u><u>a</u><u>n</u><u>s</u><u>w</u><u>e</u><u>r</u>
<u>s</u><u>u</u><u>b</u><u>s</u><u>t</u><u>i</u><u>t</u><u>u</u><u>t</u><u>i</u><u>n</u><u>g</u><u> </u><u>value</u><u> </u><u>of</u><u> </u><u>y</u><u> </u><u>in</u><u> </u><u>equation</u><u> </u><u>1</u>
<u>1</u><u>6</u><u>-</u><u>y</u><u>=</u><u>4</u>
<u>1</u><u>6</u><u>-</u><u>4</u><u>=</u><u>y</u>
<u>y</u><u>=</u><u>1</u><u>2</u><u> </u><u>a</u><u>n</u><u>s</u><u>w</u><u>e</u><u>r</u>
Answer:
12
Step-by-step explanation:
560-500=60
60/500*100=12
Answer:
D im pretty sure
Step-by-step explanation:
If each line is 20 x 3 = 60 12 dots 60 + 12 = 72 divided by 3 circles = 24
A=1/2*b*h
A=1/2*3*11
A=1/2*33
A=16.5
I hope this helps!
~kaikers
We know that
the formula for the <span>arithmetic sequence is
</span><span>an = a1 + (n - 1)*d
where
a1 is the first term
n is the numbers of terms
for n=3 a3=-8
-8=a1+(3-1)*d-----> -8=a1+2*d-----> equation 1
for n=7 a7=32
-32=a1+(7-1)*d----> -32=a1+6*d----> equation 2
multiply equation 2 by -1-----> 32=-a1-6*d------> equation 3
add equation 1 and equation 3
</span>-8=a1+2*d
32=-a1-6*d
----------------
24=-4*d------> d=-6
-8=a1+2*(-6) (substitute the value of d in equation 1)
-8=a1-12-----> a1=-8+12-----> a1=4
the answer is
a1=4
d=-6
<span>
</span>